2020
DOI: 10.1007/s00464-020-07796-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and patient satisfaction of single-session transoral incisionless fundoplication and laparoscopic hernia repair

Abstract: Background and aims Transoral incisionless fundoplication (TIF) is an effective endoscopic treatment for refractory GERD with small or absent hiatal hernia (< 2 cm in length and width). The single-session laparoscopic hernia repair followed by transoral incisionless fundoplication (HH + TIF) aims to repair mechanical defects in the lower esophageal sphincter that leads to GERD in patients with hiatal hernias ≥ 2 cm. The procedure effectively treats GERD without causing added postsurgical dysphagia and gas bloa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Another study of 99 GERD patients with HH 2 to 5 cm undergoing this combined approach showed a considerable improvement in reflux symptoms with no long-term bloating or dysphagia, which are well-known side effects after LNF at 12 months 24 . A recent retrospective study of 33 patients also demonstrated that over 80 % of patients were off PPI, and over 90 % of patients achieved greater than 75 % satisfaction after this combined approach at a median follow-up of 9 months 25 . The U.S. Food and Drug Administration expanded the indication for TIF to use in patients with HH larger than 2 cm in whom laparoscopic HH repair is performed.…”
Section: Introductionmentioning
confidence: 92%
“…Another study of 99 GERD patients with HH 2 to 5 cm undergoing this combined approach showed a considerable improvement in reflux symptoms with no long-term bloating or dysphagia, which are well-known side effects after LNF at 12 months 24 . A recent retrospective study of 33 patients also demonstrated that over 80 % of patients were off PPI, and over 90 % of patients achieved greater than 75 % satisfaction after this combined approach at a median follow-up of 9 months 25 . The U.S. Food and Drug Administration expanded the indication for TIF to use in patients with HH larger than 2 cm in whom laparoscopic HH repair is performed.…”
Section: Introductionmentioning
confidence: 92%
“…TIF is being evaluated as an option for patients with larger hiatal hernias as part of a concomitant TIF/laparoscopic hiatal hernia repair. 26 Evidence base for TIF Several randomised controlled trials have evaluated the role of TIF 2.0 in the treatment of GORD. The RESPECT study was a randomised placebocontrolled trial comparing TIF to sham.…”
Section: Esophyxmentioning
confidence: 99%
“…TIF 2.0 is suitable for patients with Hiatal hernia’s equal or less than 2 cm in size with a Hill grade equal or less than 2. TIF is being evaluated as an option for patients with larger hiatal hernias as part of a concomitant TIF/laparoscopic hiatal hernia repair 26…”
Section: Plication Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the cTIF data comes from small retrospective series [17]. Idhe et al [18] first reported on 18 patients who underwent cTIF with improvement in GERD-HRQL scores and RSI score and no adverse events.…”
Section: Outcomes With Concomitant Laparoscopic Hiatal Hernia Repair ...mentioning
confidence: 99%